ANALISIS KUALITAS SISTEM INFORMASI AKUNTANSI PADA SKPK DI LHOKSEUMAWE: PENDEKATAN ANALISIS DESKRIPTIF - Salsabila, Cut Inas; Yusmita, Fifi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study aims to determine the accounting information system on the SKPK in the city of Aceh province. Respondents who became the object of this study were Financial Administration Officers and PPK assistants in the city of Lhokseumawe, this study used a combination method. The results showed that 1) The accounting information system in the Lhokseumawe City SKPK can be used to solve problems in recording and preparing financial reports, 2) Information Technology in Lhokseumawe City SKPK has been implemented properly, 3) E-commerce website can be accessed and used by Lhokseumawe City SKPK, 4) Cloud computing in Lhokseumawe City SKPK has been implemented well.